Gradient and Scattering Forces on a Kerr Nanosphere - Pobre, R. F.; Saloma, C. A. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
A theoretical model that computes both for the gradient and scattering forces being exerted on a nonresonant nonlinear (electro-optic Kerr effect) rigid nanosphere by a strongly focused continuous-wave laser beam is presented. The incident wavelength of the laser beam is assumed to be appreciably larger than the nanosphere radius a. Optical forces arising from the aforesaid interaction can be derived by a two-component approach which determines individually the gradient force and scattering force. The behavior of the trapping (gradient) force is plotted against several experimental parameters, e.g., incident beam power, axial distance, sphere radius, wavelength, and refractive index difference between the surrounding liquid and the nanosphere. Results have shown that the Kerr effect on the nanosphere can produce a maximum of tenfold increase in the trapping force.